Analysis of Pentagon Fraud Determinants in Detecting Fraudulent Financial Statements of Banking Sector Companies Listed on the Indonesian Stock Exchange - Hasbi, Hasbi; Lala, Andi Ajeng Tenri; Asgar, Asgar (Kunuz: Journal of Islamic Banking and Finance, 2024)
Fraudulent financial statements refer to intentional negligence or errors in the preparation of financial statements, where the presentation of these statements deviates from established accounting principles. One of the theories that explain the occurrence of fraud is the Fraud Pentagon Theory. This study aims to analyze the impact of financial targets, financial stability, external pressure, ineffective monitoring, industry nature, and auditor changes on fraudulent financial statements, both partially and simultaneously. The data used in this study is secondary data, and the sampling method applied is purposive sampling. The subject of this research consists of financial information from banking sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. A total of 10 banking companies over 5 years resulted in 50 samples. The analysis techniques employed include quantitative analysis, specifically descriptive analysis, static panel data analysis, model selection, and hypothesis testing, using Eviews 10 and 12 software. The study's findings indicate that the variables of Financial Targets, Financial Stability, Ineffective Monitoring, and Nature of Industry do not significantly affect fraudulent financial statements. Conversely, the variables of External Pressure and Changes in Auditors have a positive impact on fraudulent financial statements. Simultaneously, all six independent variables collectively influence fraudulent financial statements. Consequently, alternative solutions are needed to address fraud, such as the implementation of stricter policies related to auditing and financial transparency. These measures can help minimize external pressures that encourage fraud, while the effective implementation of sustainable development goals can play a role in preventing fraud.